David Gilbert (1942)
M.V. ''Adsum'' tied up at the wharf and schooner ''Bride and Annie Dunphy'' at anchor This collection contains copies made in 1998 of original photographs gathered by the Haystack Reunion Committee for publication in their booklet Haystack Reflections (1997).